﻿Detection of sarcoidosis associated fasciitis by uptake on a FDG PET scan: a novel finding - ﻿Kalkanis, A.G.; ﻿Kalkanis, D.G.; ﻿Polychronopoulos, V.S.; Judson, M.A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
We report a case of a sarcoidosis patient with bilateral calf and thigh stiffness who was noted to ha ve intense linear FDG uptake on a PET scan that localized to the fascia of his calves and theighs. His serum creatine kinase level was normal. Fasciitis has rarely been reported to be detected on FDG PET scans, and, to our knowledge, never in a sarcoidosis patient. FDG PET may have a role in identifying fasciitis or myositis when a patient has muscular complaints and no clinical or laboratory evidence of muscle injury.